The Effect of Product Quality and Service Quality on Customer Satisfaction at PT Salad Segar Lestari (SaladStop!) Branch Grand Indonesia Jakarta - Dipayanti, Kris; Candra, Asep (Adpebi Science Series, 2022)
This study aims to determine the effect of Product Quality and Service Quality on SaladStop Customer SatisfactionAt PT. Salad Segar Lestari Branch Grand Indonesia Jakarta. Method with associative type of research with quantitativeapproach, The population in the study amounted to 28,782 customers with The sample used was 100 respondents. .The results of this study can be concluded that Product Quality has a positive and significant influence on CustomerSatisfaction where the acquisition of t values is calculated > t table (10, 895 > 1,660) and sig. <0.0 (0.000<0.1). ServiceQuality has a positive and significant influence on Customer Satisfaction where the acquisition of t values is calculated> t table (1,934 > 1,660) and sig. <0.0 (0.000<0.1). Product Quality and Service Quality simultaneously affectCustomer Satisfaction where a calculated value of 71,633 > a ftable of 3,090 and a sig. <0.1 (0.000<0.1). The multiplelinear regression equation Y= 0.564Y + 0.716X1 + 0.305X2 which means the constant value is 0.564 the value of X10.716, the value of X2 is 0.305. Based on the calculation results, it is known that the coefficient of determination (R2)obtained is 0.596 which means 59.6% Customer Satisfaction can be explained by the variables Product Quality (X1)and Service Quality (X2) while the remaining 40.4% Customer Satisfaction (Y) is influenced by variables that werenot studied in this study